Silica-Coated Magnetic Nanocomposites for Pb2+ Removal from Aqueous Solution - Roxana Nicola; Otilia Costişor; Mihaela Ciopec; Adina Negrea; Radu Lazău; Cătălin Ianăşi; Elena-Mirela Picioruş; Adél Len; László Almásy; Elisabeta I. Szerb; Ana-Maria Putz (Applied Sciences, 2020)
Magnetic iron oxide-silica shell nanocomposites with different iron oxide/silica ratio were synthesized and structurally characterized by Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), small-angle neutron scattering, magnetic and N2-sorption studies. The composite that resulted with the best properties in terms of contact surface area and saturation of magnetization was selected for Pb2+ adsorption studies from aqueous media. The material presented good absorption capacity (maximum adsorption capacity 14.9 mg·g−1) comparable with similar materials presented in literature. Its chemico-physical stability and adsorption capacity recommend the nanocomposite as a cheap adsorbent material for lead.